1987
DOI: 10.1557/proc-114-97
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of the Transition Zone to the Strength of High Quality Silica Fume Concretes

Abstract: The strength of high strength silica fume concretes is usually attributed to the reduction in w/c ratio and the refinement of the pore structure. A study of concretes and pastes, with and without silica fume, suggests that the contribution of the silica fume to strength is also the result of the densification of the transition zone. It is argued here that this influence is as important as the one due to the reduction in w/c ratio. It is suggested that the densification of the transition zone is the result of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 3 publications
1
16
0
1
Order By: Relevance
“…5). According to Bentur et al [8], this is mainly due to the aggregate-paste bond improvement and enhanced microstructure. That is to say, the strength of SF mortar is greater than that of SF paste due to the change in the role of the aggregate in mortar.…”
Section: Effect Of Sf On Compressive Strengthmentioning
confidence: 99%
“…5). According to Bentur et al [8], this is mainly due to the aggregate-paste bond improvement and enhanced microstructure. That is to say, the strength of SF mortar is greater than that of SF paste due to the change in the role of the aggregate in mortar.…”
Section: Effect Of Sf On Compressive Strengthmentioning
confidence: 99%
“…They concluded that the higher strength mortar must be due to improved bond strength between paste and sand and that the improved bond was due to the conversion of calcium hydroxide, which normally forms preferentially at the surface of aggregate particles, to calcium 3 silicate hydrate due to the presence of reactive silica. Rosenberg and Gaidis ( 1989), Bentur et a!. (1988), and Goldman and Bentur (1989) made similar observations for concrete.…”
Section: Introductionmentioning
confidence: 69%
“…There is also ample evidence that the use of silica fume results in a denser interface between cement paste and coarse aggregate (Regourd 1985, Bentur and Cohen 1987, Bentur, Goldman and Cohen 1988. Some researchers have offered indirect evidence indicating that the strength increase that occurs with the addition of silica fume to concrete is the result of an increase in bond strength between hydrated cement paste and aggregate , Rosenberg and Gaidis 1989, Goldman and Bentur 1989.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because both metakaolin and silica fume has a high specific surface area, this provides a preferential surface for absorbing the calcium ions. The removal of calcium ions from the vicinity of the cement particles accelerates the hydration of the clinker minerals [8] . At the same time, the accelerated cement hydration and the metakaolin and silica fume pozzolanic hydration activate the hydration of fly ash.…”
Section: Compensation Of Mk or Sf To High Volume Fly Ash Concretementioning
confidence: 99%